Serat Kalatidha Sebagai Kritik Ronggowarsito Terhadap Paradigma Relativisme - Yulianto, Mohammad Eka; Kuswanjono, Arqom; Utomo, Agus Himmawan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Truth is an issue that cannot be separated from all human actions in their lives. However, in line with the development of human thought, truth becomes an issue that continues to be questioned in line with its development by viewing truth from many perspectives that are relative to its truth. The existence of relative truth has consequences that place evil can also be viewed relatively, thus making humans victims of themselves. This study is an attempt to uncover historical objects in the form of literary works written by Ronggowarsito as the last Javanese poet, entitled Serat Kalatidha. This study is a library research using a philosophical approach in achieving local wisdom concepts that reveal the messages conveyed by Ronggowarsito whose lifetime was directly confronted with the Western paradigm of thought brought by European colonialists in order to control their colonies. The paradigm that causes problems in society is caused by how rationality is placed as the peak of human intellectuality, but on the other hand rationality is also the basis for the paradigm of secularism and relativism. Relativism is a paradigm based on realism in truth is a thought with forms of justification that limit the relative view to the worldly and material. This makes rationality open to being influenced by lust in making justifications that become human policies and actions. Ronggowarsito through his literary works, does not reject rationality, but is criticized and at the same time emphasized that rationality must be surpassed in order to avoid the influence of lust that traps relative morals and its 'justifications', as Javanese civilization has had the principle of absolute truth through an eling lan waspada attitude as an epistemological path to achieving awareness of the existence of spirituality in achieving the truth.